2016
DOI: 10.1080/14749009.2016.1163918
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional analysis of complex anisotropic slope instability at MMG’s Century Mine

Abstract: Anisotropic and foliated rock masses present particular difficulties in the assessment of pit slope stability. Although many attempts have been made to describe the strength of rock masses that exhibit a preferred orientation of weakness, no general methodology has emerged throughout the literature to simulate anisotropic behaviour in a three-dimensional numerical model of pit slope stability. In order to simulate the effect of the anisotropic shale rock mass on pit slope stability at MMG Limited's (MMG) Centu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…e results of deformation measurements are values in the LOS direction [14], which are limited by the InSAR measurements themselves. To obtain the real 3D deformation information of the surface, it is necessary to use simultaneous multisource data, multi-incidence angle data, etc., to obtain deformation information along more directions in the study area, so that the true 3D information of the surface can be solved with the mathematical model [4,36,37]. erefore, to obtain accurate 3D surface deformation information, more data must be processed to obtain more deformation information from different aspects, in addition to combining field measurements, retrieving missing measurements by spatial interpolation, etc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…e results of deformation measurements are values in the LOS direction [14], which are limited by the InSAR measurements themselves. To obtain the real 3D deformation information of the surface, it is necessary to use simultaneous multisource data, multi-incidence angle data, etc., to obtain deformation information along more directions in the study area, so that the true 3D information of the surface can be solved with the mathematical model [4,36,37]. erefore, to obtain accurate 3D surface deformation information, more data must be processed to obtain more deformation information from different aspects, in addition to combining field measurements, retrieving missing measurements by spatial interpolation, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Mining activity can cause surface deformations and negatively impacts the environment [1,2]. If rehabilitation measures are not handled properly, they can lead to serious subsequent disasters such as mine collapse [3], slope instability [4], vegetation death over large areas [2,5], and severe water-soil erosion [3].…”
Section: Introductionmentioning
confidence: 99%
“…Full-sized 3D models can estimate the deformations of underground openings and explore the mining-induced stress redistribution paths better than 2D analysis models [ 30 , 34 , 35 , 36 , 37 ]. Therefore, to better represent the complicated geometry of the stopes and haulages in the mining pipe at the hard rock mine, a full-sized elastoplastic three-dimensional (3D) model was developed by employing ABAQUS codes [ 38 ].…”
Section: Background and Methodologymentioning
confidence: 99%
“…Back-analysis of the fracturing limits induced by caving at El Teniente mine conducted by Cavieres et al (2003) showed that a total strain criterion of 5e-3 is a good indicator for delineation of the fracture zone limit from numerical modeling results. This criterion has been used extensively and has been validated further through back-analysis of fracture limits at Kiruna (Sainsbury & Stockel 2012), Grace (Sainsbury & Lorig 2005), Century Mines (Sainsbury et al 2016), and Cadia East (Ghazvinian et al 2020a) as well as Andina, Venetia, Lac des Isles, and Pampa Escondida (confidential reports).…”
Section: Fracture Limitmentioning
confidence: 99%